Gender Prejudice Within the Family: The Relation Between Parents' Sexism and Their Socialization Values - Barni, Daniela; Fiorilli, Caterina; Romano, Luciano; Zagrean, Ioana; Alfieri, Sara; Russo, Claudia (Frontiers in Psychology, 2022)
Gender inequalities are still persistent despite the growing policy efforts to combat them. Sexism, which is an evaluative tendency leading to different treatment of people based on their sex and to denigration (hostile sexism) or enhancement (benevolent sexism) of certain dispositions as gendered attributes, plays a significant role in strengthening these social inequalities. As it happens with many other attitudes, sexism is mainly transmitted by influencing parental styles and socialization practices. This study focused on the association between parents’ hostile and benevolent sexism toward women and their socialization values (specifically, conservation and self-transcendence), that are the values parents would like their children to endorse. We took both parents’ and children’s sex into account in the analyses. One-hundred-sixty-five Italian parental couples with young adult children participated in the study. Parents, both the mother and the father, individually filled in a self-report questionnaire composed of the Ambivalent Sexism Inventory and the Portrait Values Questionnaire. Findings showed that mothers’ benevolent sexism was positively related to their desire to transmit conservation values to their sons and daughters. This result was also found for fathers, but with a moderation effect of children’s sex. Indeed, the positive relationship between fathers’ benevolent sexism and conservation was stronger in the case of sons than of daughters. Moreover, fathers’ benevolent sexism was positively associated with self-transcendence values. Finally, fathers’ hostile sexism was positively associated with conservation and negatively with self-transcendence. Limitations of the study, future research developments, and practical implications of the results are discussed.